The Wellbeing of Year 13 Girls in High-Decile, High Performing, Single-Sex Secondary Schools in New Zealand - Whitham-Blackwell, Nicola Jane (Auckland University of Technology, 2017)
The aim of this research was to investigate the wellbeing of Year 13 girls in high-decile, high performing single-sex schools. It was based on a rationale that the wellbeing of this group of students is suffering, and that the three-year continuous assessment system – the National Certificate of Educational Achievement - in New Zealand secondary schools, comprising of both internal and external assessments, is adding to the lack of balance in their lives. Worldwide there exists an increasing concern about the wellbeing of high school students. In tandem, there is a growing focus on achievement as students compete for places in universities, and schools compete for students. Many parents make decisions about their children’s high school education based on achievement data from schools. What seems to be missing is a focus on the holistic needs of young people, what we in New Zealand call ‘hauora’. Overseas literature suggests that students in high socio-economic communities are the most vulnerable when it comes to stress and anxiety, with high performing girls’ schools at the top of that list. Based on the current literature from the New Zealand context, the wellbeing of school students as a topic, apart from some emerging government documents, is notable by its absence. This qualitative research project involved five focus groups and four interviews with a total of 22 participants across three different schools in two different cities in New Zealand. The study found that the experience of these students is one of almost constant stress and pressure, with significant social, emotional, physical and mental health consequences. This pressure is exacerbated by problems with inconsistencies in the administration and assessing of NCEA, by expectations from all sides - including from the school, their parents, their peers and themselves - and by over-assessment and badly planned assessment timetables. The challenges for school leaders going forward are myriad. Ways need to be found to reduce the constant pressure on these students. In particular, attention needs to be paid to avoiding over-assessment, avoiding assessment clashes, and creating a culture where students feel supported, valued and understood. Expectations need to be monitored across subjects and across groups in these young women’s lives. Both teachers and parents need to be educated in the realities of these students’ experiences of school, and schools must make real efforts to listen to the voices of these students. It is necessary for both schools and the government to take action to alleviate the stress, pressure and anxiety that many of these students experience all too regularly.
Keywords: Secondary school students; Wellbeing; NCEA; Feminist paradigm